2006
DOI: 10.1002/ejic.200500700
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Hydrogen‐Bond‐Mediated Exchange Coupling in an Aqua‐Bridged CuII Dimer: Synthesis, Magnetic Study and Correlation with Density Functional Calculations

Abstract: Keywords: Bridging ligands / Copper / Density functional calculations / Exchange interactions / Hydrogen bondsA rare example of a mono-aqua-bridged copper(II) dimer,, has been synthesised and its structure determined by single-crystal Xray diffraction. Each Cu II centre is in a square-pyramidal surrounding formed by a Schiff base and a terminal H 2 O ligand; a second H 2 O ligand, which acts as a bridge, is common to two metal ions. Hydrogen bonds between the H 2 O ligand and the Schiff base of the adjacent ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…However, to the best of our knowledge only four single [15,[20][21][22] aqua-bridged Cu(II) complexes are reported in the literature. It is interesting to note that each unit within the dimer are also connected to each other through strong H-bonds.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, to the best of our knowledge only four single [15,[20][21][22] aqua-bridged Cu(II) complexes are reported in the literature. It is interesting to note that each unit within the dimer are also connected to each other through strong H-bonds.…”
Section: Introductionmentioning
confidence: 84%
“…Although the aqua ligand usually exhibits the terminal coordination mode in copper(II) complexes, but complexes in which H 2 O acts as a bridge are also well known [15][16][17][18][19]. However, to the best of our knowledge only four single [15,[20][21][22] aqua-bridged Cu(II) complexes are reported in the literature.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The versatile features of metal-azido and metal-thiocyanato systems in coordination chemistry may lead to novel structures that are difficult to obtain with other bridging ligands, but a major obstacle is impossible to predict which coordination modes will be adopted by the azide and thiocyanate ligands. During the search of literature, we found that the copper(II) complexes derived from the tridentate Schiff base ligands 2-[1-(2-dimethylaminoethylimino)ethyl]phenol and N,N-dimethyl-N 0 -(1-pyridin-2-ylethylidene)ethane-1,2-diamine have been extensively studied [11][12][13][14][15], however, no complexes have been reported for the similar tridentate Schiff base ligands 2-[1-(2-methylaminoethylimino)ethyl]phenol (HL 1 ; Scheme 1) and N-methyl-N 0 -(1-pyridin-2-ylethylidene)ethane-1,2-diamine (L 2 ; Scheme 1). In continuation of the work on the azide and thiocyanate-bridged complexes with Schiff bases, a new end-to-end thiocyanato-bridged 1D polymeric copper(II) complex [CuL 1 (l 1,3 -NCS)] n (1), and a new end-on azido-bridged dimeric copper(II) complex [CuBrL 2 (l 1,1 -N 3 )] 2 (2), were synthesized and structurally characterized.…”
Section: Introductionmentioning
confidence: 99%